Corporate governance, audit recommendations, and financial resilience: the case of state-owned Indonesian mining and energy enterprises / Daniel Lumban Tobing, Purwatiningsih Lisdiono and Zuraidah Mohd Sanusi - Tobing, Daniel Lumban; Lisdiono, Purwatiningsih; Mohd Sanusi, Zuraidah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
This study examined how corporate governance and audit recommendations affected the financial resilience of Indonesian state-owned enterprises’. For five years, 2018–2022, 20 SOEs were studied. The period was chosen to reflect before, during, and after the pandemic. SPSS processed data using OLS. The results showed that board effectiveness and audit recommendations positively and significantly influenced financial resilience. Board effectiveness, in this study, measured by board number, affected an organization’s decision-making and strategic outcomes. The auditor’s recommendations assisted decision-makers in uncovering and preventing errors, irregularities, fraud, and inefficient practices, fixing deficiencies, and monitoring improvement. However, the hypothesis that government ownership influenced financial resilience was not supported. The findings have extended the growing literature on monitoring mechanisms in the Agency Theory to improve financial resilience and the SAIs activities in SOEs in emerging countries. This study contributes to practical implications such as understanding performance audits and audit recommendations done by the Indonesia Supreme Audit Institution and giving the recommendations to regulators to develop world-class and effective SOEs.